Zero space : moving beyond organizational limits - Deprez, Frank Lekanne (Berrett-Koehler Publishers, 2002)
"'Zero Space' defines a business model in which an organization achieves success without owning assets or needing management. Through eight new organizational principles the authors illustrate how 'zero-mindedness' is essential for the new economy"--Resource description page.